المعالجة الصحفية لموضوعات مجزرة سبايكر في موقع الفرات نيوز: دراسة تحليلية للمدة من "2014/6/15 ولغاية 2017/12/31" - الأسدي، محمد فالح حسن (جامعة بابل - مركز بابل للدراسات الحضارية والتاريخية, 2024)
يهدف البحث إلى معرفة مديات معالجة الصحافة الإلكترونية متمثلة بموقع الفرات نيوز لموضوعات مجزرة سبايكر، والتعرف على اتجاه الموقع إزاء هذه المجزرة، فضلا عن معرفة مدى دقة ومصداقية وموضوعية الموقع في معالجته لموضوعات المجزرة، والكشف عن الأساليب التي استخدمتها الصحافة الإلكترونية متمثلة بهذا الموقع في معالجة هذه الموضوعات، لذا استخدم الباحث المنهج الوصفي كونه من أنسب المناهج المستخدمة في الدراسات الإعلامية، إذ يساعد في وصف الأحداث وتحليلها بشكل دقيق بالاعتماد على أسلوب تحليل المضمون، بحصر موضوعات مجزرة سبايكر جميعها للمدة من 15/٦/٢٠١٤م- 31/۱۲/۲۰۱۷م، إذ قام الباحث بتحليل المضامين وفقا لاستمارة أعدت لهذا الغرض والتي تضمنت فئات (ماذا قيل، وكيف قيل)، وبعد الحصول على النتائج الكمية والنوعية للتحليل وتفسير النتائج، توصل الباحث إلى استنتاجات متعددة أبرزها أن موقع مجتمع البحث ركز على أن الأسباب الحقيقة التي قتل على أثرها الشباب في مجزرة سبايكر كانت على الأساس المذهبي والطائفي، متجاهلا الصراعات السياسية والخروقات الأمنية ووجود التنظيمات الإرهابية سبب لحدوث المجزرة، واعتمد الموقع على الأخبار البسيطة بالاعتماد على نقل البيانات والتصريحات الرسمية في نقل الأخبار دون إجراء التقارير والتحقيقات المعمقة حول الموضوع، وأيضا التعامل المذهبي إزاء المجزرة، وأن موقع مجتمع البحث ركز على الوسائط المتعددة (الصور) في الأخبار، وابتعد عن استخدام الفيديوهات بسبب الطرق البشعة لعمليات القتل، وأظهر موقع مجتمع البحث الموقف السلبي للحكومة العراقية المتمثل في حصر أعداد الضحايا فقط دون الكشف عن حقائق حدوث المجزرة، واهتم الموقع بموضوع إصدار الأحكام القضائية بحق المتورطين في المجزرة في المركز والمطالبة بالقصاص العاجل لمن قتل الشباب الشيعة، وعمد موقع مجتمع البحث على نشر موضوعات مجزرة سبايكر في الصفحة الرئيسة وذلك لأهمية الحدث كونه من الأحداث المحلية المهمة التي شغلت الرأي العام المحلي. The aim of this research is to seek knowledge about the process of electronic journalism, represented by the Al-Furat News website about the topics of the Spiker massacre, and to identify the site’s direction regarding this massacre. In addition for recognition the accuracy, credibility and objectivity of the site in its treatment of the massacre topics. And to reveal the methods used by the electronic press, represented by this website, in dealing with these topics. Therefore, the researcher used the descriptive method, as it is one of the most appropriate methods used in media studies. It helps in describing the events and analyzing them accurately, relying on the content analysis method, by listing all the topics of the Spiker massacre for the period from 15/6/2014 AD- 31/12/2017 AD. The researcher analyzed the contents according to a form prepared for this purpose, which included categories (what was said, and how was it said). After getting the quantitative and qualitative results to be analyzed and interpreted, the researcher reached several conclusions, the most notable one is: The research community website focused on the fact that the real reasons for which young men were killed in the Spiker massacre were on a sectarian and doctrine basis. Ignoring the political conflicts, security breaches, and the presence of terrorist organizations as a reason for the massacre, so the site relied on simple news, by transferring official data and statements to convey the news without conducting in-depth reports and investigations about the topic. As well as the sectarian response to the massacre, and the research community’s website focused on multimedia (images) in the news. Furthermore, the site did not use videos because of the horrific methods of killing. The research community website showed the negative attitude of the Iraqi government in counting only the numbers of victims without revealing the facts of the massacre. The site focused on the issue of court rulings against those involved in the massacre at the center and demanding urgent retribution for those who killed Shiite youth. The research community website decided to publish the topics of the Spiker massacre on the main page due to the importance of the event, being one of the important local events that occupied local public opinion.
Keywords: الصحافة الرقمية -- التنظيمات الإرهابية -- المواقع الصحفية -- العراق